Minimizar stocks no retalho automóvel: análise preliminar de dados - Ribeiro, David Garcia (2019)
Consumers would like to acquire vehicles with certain characteristics and do not want to wait for those vehicles to be built, due to the production lead-times. Therefore, the dealerships have a certain number of vehicles in stock with feature combinations such as colours, alloy wheels and car navigation features. In this paper, a data collection is presented with the objective of understanding which features are desired by the consumers, that data was comparatively analysed with data from actual sales, to validate if those preferences are aligned with real vehicles sales. Thus, this study will help dealerships to order vehicles to stock based with consumer preferences with the goal to sell vehicles rapidly and consumers become more satisfied.